Gendered perspectives on economic growth and development in sub-Saharan Africa - Stephanie Seguino; Maureen Were (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Researchers have linked sub-Saharan Africa's (SSA) poor growth performance in recent decades to several factors, including geography, institutions, and low returns to investment. This literature has not yet integrated the research that identifies linkages between gender, economic development, and growth, however. This paper explores the macro effects of gender, transmitted via the productive sector and in the household, in part due to the tendency for work - paid and unpaid - to be gender-segregated. Macro-level policies in turn can have differential effects on men and women. Evidence that gender equality is itself a stimulus to growth in a number of SSA countries underscores the importance of assessing the gender effect of macroeconomic policies.
Keywords: O1; E24; E25; J16; 330; gender; economic development; growth; sub-Saharan Africa; macroeconomic models; fiscal policy